Using Interactive Technology to Disseminate Research Findings to a Diverse Population - Denise Stockley; Wanda Beyer; Nancy Hutchinson; Jennifer DeLugt; Peter Chin; Joan Versnel; Hugh Munby (The Canadian Network for Innovation in Education (CNIE), 2009)
This paper demonstrates how case stories can be used to disseminate the findings of several case studies on negotiating accommodations in the workplace. It highlights the power of interactive technology and of the partnership between the researchers and the Canadian Council for Rehabilitation and Work (CCRW). The paper describes the process of designing an interactive web-based case story for the purpose of disseminating research findings. The interactive case story is an extension of both the case study and the narrative case story. As part of a larger research project, it is our goal to use interactive case stories to investigate the impact of essential skills training on workers with disabilities who negotiate with employers for workplace accommodations. Résumé Le présent article montre comment les histoires de cas peuvent être utilisées pour diffuser les conclusions de plusieurs études de cas sur la négociation entourant l'aménagement du milieu de travail. Il met en évidence le pouvoir de la technologie interactive et du partenariat entre les chercheurs et le Conseil canadien de la réadaptation et du travail (CCRT). L'article décrit le processus de conception d'une histoire de cas interactive en ligne visant à diffuser des résultats de recherche. L'histoire de cas interactive est un prolongement à la fois de l'étude de cas et du récit de l'histoire de cas. Dans le cadre d'un plus vaste projet de recherche, notre but est d'utiliser des histoires de cas interactives pour étudier l'impact de la formation sur les compétences essentielles chez les travailleurs handicapés qui négocient avec leur employeur pour l'aménagement de leur milieu de travail.